Production of Amylase from Aspergillus niger under Solid State Fermentation (SSF) with different Agro Waste as the Substrates - Pavithra, Madheuan (Universiti Malaysia Sarawak, (UNIMAS), 2018)
Agricultural wastes are produced by agricultural operations for instances are from forestry, farming, and agro-industry. Accumulation of the wastes from day to day gives impacts to human and environment. In this research, utilisation of agro-wastes which were potato peels, sweet potato peels and banana peels was done to extract amylase from Aspergillus niger by solid-state fermentation. The solid-state fermentation optimization of parameters such as incubation period, initial moisture content of substrate and incubation temperature that affecting solid-state fermentation to produce maximum amylase production in term of enzyme activity were studied. Enzyme activity was determined via Dinitrosalicylic acid (DNS) method. Among of these agricultural wastes used, the best agricultural waste to produce the highest enzyme activity was potato peel with its optimal condition of 6 incubation days, 70% moisture content and 35°C with activity of 0.148 U.